TEACHING ENGLISH TO YOUNG LEARNERS - Octaviana, Dwi Warry (Universitas Nusantara PGRI Kediri, 2017)
ABSTRACT Learning English is vital skills that will help children achieve their full potential in later life. If they have the right techniques, they can learn English quickly and effectively. So, it is important that they have to learn English which is practical and useful. Learning should not be stressful for children. It should be fun and stimulating. Their studies should make reading, listening, and speaking in English come naturally. As their confidence develops, they will learn more and use English to a more challenging level. This paper discusses about some resources for EFL teachers to facilitate the children in learning a foreign language. These are purposed for them to be able to teach effectively with the fun and variety that children need. The last part, this paper tells about how to ensure the children learn English using simple techniques that will absolutely make the teachers’ job more fun and satisfying. Also, it will be expected that the teachers will have enough fresh ideas to be the most inspiring teachers that they possibly can.